Attenuation of G(i)- and G(q)-mediated signaling by expression of RGS4 or GAIP in mammalian cells - Huang, Chunfa (The National Academy of Sciences of the USA, 1997)
Protein regulators of G protein signaling (RGS proteins) were discovered as negative regulators of heterotrimeric G protein-mediated signal transduction in yeast and worms. Experiments with purified recombinant proteins in vitro have established that RGS proteins accelerate the GTPase activity of certain G protein α subunits (the reaction responsible for their deactivation); they can also act as effector antagonists. We demonstrate herein that either of two such RGS proteins, RGS4 or GAIP, attenuated signal transduction mediated by endogenous receptors, G proteins, and effectors when stably expressed as tagged proteins in transfected mammalian cells. The pattern of selectivity observed in vivo was similar to that seen in vitro. RGS4 and GAIP both attenuated G(i)-mediated inhibition of cAMP synthesis. RGS4 was more effective than GAIP in blocking G(q)-mediated activation of phospholipase Cβ.